ANALISIS PROSPEK PERKEMBANGAN MODAL DAN TENAGA KERJA PADA INDUSTRI KECIL DI KABUPATEN SIDENRENG RAPPANG - Agus Syam (IAIN Manado, 2017)
Abstract Analysis of Prospect Capital Growth and Employment in Small Industries in The District Sidenreng Rappang. This research was conducted to answer the question